A Multiliteration-Based Scaffolded Writing Model on Learning to Write a Personal Letter at Kanggraksan Elementary School in The City of Cirebon - Rahayu, Mega Mugi; Rahman, Rahman; Sopandi, Wahyu; Sujana, Atep (International Conference on Elementary Education, 2020)
This research is based on the low student learning outcomes in learning Indonesian. From these data, the researchers used multiliterated scaffolded writing models in student writing learning. This study generally aims to obtain a picture of a series of learning to write by using a Personal Letter in class IV SD Negeri Kanggraksan. The research method used is the classroom action research (CAR) Elliot model. Data analysis techniques carried out were qualitative, quantitative and triangulation data analysis. The purpose of this study is to find out an overview of the processes and abilities of students in writing personal letters. The research subjects in this study were class IV consisting of 17 male students and 15 female students and the observer partner was the teacher in the class. From the results of the study it can be concluded that an increase in the average value of learning outcomes in each cycle increases. The average value of student learning outcomes in cycle 1 was 61.69, increased in cycle 2 to 67.70 and increased again in cycle 3 to 83,90. Based on these results it can be concluded that the ability to write personal letters using the Scaffolded writing model can improve students' writing abilities. Hopefully the results of this study will be useful in efforts to improve the quality of Indonesian education